Applicability of double Channel Technique in AlGaN/GaN HEMT for future biosensing applications. (December 2021) - Arivazhagan, L.; Nirmal, D.; Jarndal, Anwar; Huq, Hasina F.; Chander, Subhash; Bhagyalakshmi, S.; Reddy, Pavan Kumar; Ajayan, J.; Varghese, Arathy
Abstract: Sensing COVID-19, GOx (glucose oxidase enzyme) in exhaled breath condensate/saliva, bio-molecules like KIM (Kidney Injury Molecule) in human body and pH value in human body fluids have gained huge attention in the present scenario as well as in the past decade. Hence, for the first time, double channel technique in AlGaN/GaN High Electron Mobility Transistor (HEMT) is proposed and its applicability is demonstrated by biosensing application. Simulation using SILVACO Technology Computer Aided Design (TCAD) based on numerical solid state models has been extensively used for investigation and analysis. The sensitivity of double channel device is compared with single channel device and its performance is evaluated in terms of the transconductance. Unlike the single channel device, double channel device exhibited wide range of transconductance with respect to gate bias. The device recorded a sensitivity of 136%, which is 74% higher than the sensitivity of single channel device. Hence, it is inferred that the sensitivity enhances with the use of multiple channels and could be increased by increasing the number of channels. The results of this research show that the proposed sensor stands a promising candidate for future biosensing applications that demand high detection limits. Highlights: For the first time, double channel AlGaN/GaN HEMT is proposed for biosensing application. Double channel HEMT offers a sensitivity of 136%. Higher sensitivity of double channel device is attributed to the presence two channels in the device.